Pelayanan Epo (Exit Permit Only) Crewing oleh PT. Samudra Shipping Agency pada Kantor Imigrasi Dumai - Zenika Putra Fatemaluo; Yuna Sutria (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study focuses on analyzing the Exit Permit Only (EPO) Crewing Services organized by PT. Samudra Shipping Agency in cooperation with the Dumai Immigration Office. The EPO service plays a crucial role in ensuring legal compliance regarding the movement of foreign seafarers who are executing a sign-off (leaving the vessel) within Indonesian territory. The main objectives of this research are to examine the operational procedures, analyze the role of the shipping agency, and evaluate the effectiveness of the synergy between the agency and the immigration authorities in processing immigration documents. The research methodology employed is a combination of field research (field research), which involves observation and the collection of practical data, and literature review (library research) to strengthen the regulatory and theoretical foundation. The findings indicate that the success of the EPO service is highly dependent on the effective synergy between PT. Samudra Shipping Agency and the Dumai Immigration Office. The shipping agency holds a vital role in handling the entire crew sign-off process and is fully responsible for managing the temporary stay permits for foreign crew members through the issuance of a Dahsuskim (Special Immigration Document). The improvement in the quality of this EPO service not only provides operational benefits for the agency and the crew involved but also substantially supports the government's efforts to supervise the movement and presence of foreign workers in an orderly and legal manner. Optimizing this procedure will enhance efficiency and regulatory compliance in the port area.